The Education Criteria for Performance Excellence Impacting the Budget Allocation: A Case Study of Faculty of Architecture, Urban Design & Creative Arts Mahasarakham University - Mirattanaphrai, Preeyanat; Poonpool, Nuttavong; Khiewsued, Yada (Arts of Management Journal, 2024)
The purpose of this research was to study 1) the results of performance education criteria for performance excellence of the Faculty of Architecture, Urban Design & Creative Arts Mahasarakham University; 2) the education criteria for performance excellence for budget allocation and management of the Faculty of Architecture, Urban Design & Creative Arts Mahasarakham University; and 3) present guidelines for management and budget allocation of the Faculty of Architecture, Urban Design & Creative Arts Mahasarakham University. To do so, the researcher collected data from 1) a source of information from the annual report of the faculty and information on the results of operations according to educational quality criteria for excellent operations during the academic year 2019-2022 and 2) senior executives of the Faculty of Architecture, Urban Design & Creative Arts, Mahasarakham University. The research results showed that the following was found: 1) Education Criteria for Performance Excellence Topics: five results include student learning, customer-focused service results, the process results, customer results, workforce results, leadership and governance results, and budgetary, financial, market, and strategy. 2) The interview results are a budgetary, financial, market, and strategy analysis of the overall budget allocation of the Faculty of Architecture, Urban Design & Creative Arts, Mahasarakham University. Therefore, guidelines for management and budget allocation senior executives should be aware of and give importance to systematically creating results, and approaches to advance proactive projects to the faculty must be able to correspond to the indicators of educational quality criteria for excellent performance in each outcome area and create innovations for sustainability.